Efficient Photocatalytic Hydrogen Evolution via Cocatalyst Loaded Al-doped SrTiO3 - Zh. Kuspanov; A. Serik; A. Baratov; U. Abdikarimova; N. Idrissov; M. Bissenova; Ch. Daulbayev (Eurasian Chemico-Technological Journal)
The growing reliance on fossil fuels is causing significant environmental issues, prompting the search for renewable energy sources. Hydrogen energy, which produces only water vapor, is a promising solution. This study focuses on developing an aluminum-doped SrTiO3 photocatalyst with dual cocatalysts (Rh/Cr2O3 and CoOOH) for efficient photocatalytic water splitting. Using a simple chemical deposition method, high-purity and crystalline SrTiO3 was synthesized and thoroughly characterized. The results show that the modified SrTiO3 achieved significantly higher photocatalytic activity, with Rh/Cr2O3/SrTiO3@Al/CoOOH producing 11.04 mmol g–1 h–1 of H2 and 4.69 mmol g–1 h–1 of O2. This work demonstrates the effectiveness of dual cocatalyst deposition and aluminum doping in enhancing photocatalytic performance by improving charge separation and reducing recombination.